Intervenções da prática educacional-confessional para a formação dos discentes de uma instituição de educação superior adventista - Azevedo, Zanin, Henrique de (2021)
The Adventist Educational Network, which is historically and philosophically linked to the religious precepts of the Seventh-day Adventist Church, is among many educational-confessional proposals for higher education. Therefore, this research is an analysis of the practices conducted by Adventist educational-confessional for higher education in the formation process of their students. For this purpose, the most preeminent Adventist institution in Brazil – UNASP Centro Universitário Adventista de São Paulo – was chosen to carry out this research. The analysis of official documents and interviews with students from this institution used Oral History as a methodological basis and the theoretical hermeneutic key found in the strategic and tactical categories, proposed by Michel de Certeau. In other words, in this study, the theological-philosophical-educational foundations of the Adventist Education for higher education were examined from the perceptions of daily practices experienced by students. The collaborators' speeches present considerations, evaluations, criticisms, and a stream of meanings for several themes coming from the current confessional model.(AU)